Загальні засади короткострокового піклування (патронатного піклування) над дітьми за законодавством Чеської Республіки - Зубанич, О. В.; Zubanych, O. V. (Право і суспільство. – 2020. – № 4. – С. 61-72, 2020)
Стаття присвячена аналізу загальних засад короткострокового піклування над дітьми (патронатне піклування), які внаслідок певних життєвих обставин залишились без родинного піклування або отримують неналежне родинне піклування в Чеській Республіці. На підставі проведеного дослідження правових засад організації та діяльності короткострокового піклування (патронатного піклування) в Чеській Республіці автором встановлено, що інститут патронату за законодавством Чеської Республіки встановлюється на строк не більше 1 року, зазначений строк є максимальним і продовженню не підлягає. Найчастіше цей інститут застосовується щодо дітей, в тому числі новонароджених, батьки яких тимчасово не можуть про них піклуватися внаслідок хвороби, лікування від алкогольної або наркотичної залежності, перебування в пенітенціарних закладах, поганого психічного стану, зокрема, поганого або хворобливого психічного стану матері, пов’язаного з післяпологовою депресією, або поганого соціального стану, зокрема, відсутності у батьків можливостей для належного перебування дитини (наприклад, бездомні батьки), щодо дітей, над якими знущались батьки,покинутих або знайдених дітей, новонароджених дітей, батьки яких не хочуть забирати дитину з пологового будинку. Патронатні вихователі є професійними вихователями, які отримують заробітну плату за свою роботу та повинні відповідати певним критеріям, встановленим законом, пройти навчання, перебувати у відповідному реєстрі осіб, які можуть надавати патронатну допомогу. The article is devoted to the analysis of the general principles of short-term care for children who, as a result of certain life circumstances, have been left without family care or receive inadequate family care (foster care) in the Czech Republic. Patronage over a child frst appeared in the legislation of Ukraine four years earlier than in the legislation of the Czech Republic (in 2002 in Ukraine against 2006 in the Czech Republic), but its intensive use in the Czech Republic began four years earlier than in Ukraine (from 2013 in the Czech Republic against 2017 in Ukraine), which determines the relevance of the study of this institution of family law in the Czech Republic. In addition, a separate study of the principles of short-term child care under the legislation of the Czech Republic in Ukraine was not conducted. Therefore, the aim of the article is to acquaint the legal community with the basic legal principles of the organization and activities of short-term care (foster care) in the Czech Republic, as a member of the European Union. Based on a study of the legal basis for the organization and activities of short-term care (patronage care) in the Czech Republic, the author found that the institution of patronage under the legislation of the Czech Republic is established for a period not exceeding 1 year, this period is maximum and cannot be extended. Most often, this institution is applied to children, including newborns, whose parents are temporarily unable to care for them due to illness, treatment for alcohol or drug addiction, stay in prisons, poor mental state, such as poor or painful mental state of the mother. With postpartum depression, etc., or poor social status, such as the lack of opportunities for parents to have a proper child (for example, homeless parents), children abused by parents, abandoned or found children, newborns whose parents do not want to take the child from maternity hospital. Foster carers are professional educators who receive a salary for their work, which must meet certain criteria established by law, undergo training, be in the appropriate register of persons who can provide foster care. Цель статьи - проанализировать и охарактеризовать общие основы краткосрочного попечительства (патронатного попечительства) по законодательству Чешской Республики. Для достижения поставленной цели необходимо исследовать нормативно-правовые акты Чешской Республики, касающиеся порядка и принципов существования института семейного права - краткосрочнй опеки.
The general principles of short-term care for children who, as a result of certain life circumstances, in the Czech Republic
Зубанич, О. В. Загальні засади короткострокового піклування (патронатного піклування) над дітьми за законодавством Чеської Республіки / Зубанич, О. В. // Право і суспільство. – 2020. – № 4. – С. 61-72. - DOI: https://doi.org/10.32842/2078-3736/2020.4.9.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Сімейне право. Family law. Семейное право; Чеська Республіка; Чешская Республика; Czech Republic; короткострокове піклування; краткосрочное попечительство; short-term care; патронатне піклування; патронатний вихователь; патронатный воспитатель; foster carer; правове регулювання; правовое регулирование; legal regulation; діти; дети; children; зарубіжний досвід; зарубежный опыт; foreign experience